(untitled) (Faridpur Medical College Journal, 2011)
Laparoscopic cholecystectomy has become the gold standard treatment for symptomatic gallbladder disease. Its role in surgical treatment of acute cholecystitis has also been well defined. Here a prospective study was conducted over a 3 year period of 28 patients with acute cholecystitis at district level hospitals of Bangladesh, where many modern surgical facilities were lacking. Out of 28 patients of acute cholecystitis, 24 were operated by laparoscopic methods and rests 4 were converted to open cholecystectomy. Mean operation time was 87.95 minutes and only 2 patients had postoperative complications. This study showed the appropriate time of laparoscopic cholecystectomy for acute cholecystitis, conversion rate and complications. It may be concluded that laparoscopic cholecystectomy is feasible and beneficial to the patient with acute cholecystitis in its early phase, if necessary support and expertise is available. Key Words: Acute cholecystitis; Laparoscopic cholecystectomy; Conversion DOI: 10.3329/fmcj.v5i1.6804 Faridpur Med. Coll. J. 2010;5(1):3-6